Accessibility of DNA polymerases to repair synthesis during nucleotide excision repair in yeast cell-free extracts - Wu, Xiaohua (Oxford University Press, 2001)
Nucleotide excision repair (NER) removes a variety of DNA lesions. Using a yeast cell-free repair system, we have analyzed the repair synthesis step of NER. NER was proficient in yeast mutant cell-free extracts lacking DNA polymerases (Pol) β, ζ or η. Base excision repair was also proficient without Polβ. Repair synthesis of NER was not affected by thermal inactivation of the temperature-sensitive mutant Polα (pol1-17), but was reduced after thermal inactivation of the temperature-sensitive mutant Polδ (pol3-1) or Polɛ (pol2-18). Residual repair synthesis was observed in pol3-1 and pol2-18 mutant extracts, suggesting a repair deficiency rather than a complete repair defect. Deficient NER in pol3-1 and pol2-18 mutant extracts was specifically complemented by purified yeast Polδ and Polɛ, respectively. Deleting the polymerase catalytic domain of Polɛ (pol2-16) also led to a deficient repair synthesis during NER, which was complemented by purified yeast Polɛ, but not by purified yeast Polη. These results suggest that efficient repair synthesis of yeast NER requires both Polδ and Polɛ in vitro, and that the low fidelity Polη is not accessible to repair synthesis during NER.